Development and analytical validation of a fluorescent recombinase polymerase amplification-assay for real-time detection of Phyllosticta citricarpa, the causative agent of Citrus Black Spot - Federico La Spada; Rossana Parlascino; Mario Riolo; Sebastiano Conti Taguali; Antonella Pane; Matteo Garbelotto; Bryant Davenport; Marcos Amato; Santa Olga Cacciola (Physiological and Molecular Plant Pathology, 2026)

Effects of local management and landscape factors on taxonomic and functional diversity of multiple taxa in managed grasslands - Matteo Conti; Andrea Dalpasso; Alberto Mattia Nodari; Isabel Cantera; Benedetta Barzaghi; Mattia Brambilla; Andrea Ferrari; Gentile Francesco Ficetola; Simone Giachello; Elia Lo Parrino; Valeria Messina; Carlo Polidori; et al. (Agriculture, Ecosystems & Environment, 2026)

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Integrating single nuclei and bulk RNA sequencing in rice shoot apical meristems uncovers candidate early floral transition gene networks - Daniele Traversa; Giulio Vicentini; Paolo Korwin Krukowski; Lucio Conti; Matteo Chiara; Vittoria Brambilla (Plant Reproduction, 2025)

Sex differences in Parkinson’s disease-related non motor symptoms: a focus on sleep problems - Roberta Bovenzi; Matteo Conti; Valentino De Franco; Mariangela Pierantozzi; Tommaso Schirinzi; Rocco Cerroni; Alessandro Stefani; Nicola Biagio Mercuri; Claudio Liguori (Acta Neurologica Belgica, 2024)
Parkinson’s disease (PD) symptomatology differs between females and males, yet the contribution of sex on sleep problems needs further analysis. Here, we aimed to investigate sex-specific patterns in the relationship between sleep problems, assessed using the Parkinson’s disease sleep scale (PDSS-2), non motor symptoms (NMS), measured by the NMS scale (NMSS), and health-related quality of life (HR-QoL), evaluated by the Parkinson’s disease questionnaire (PDQ-39), in a large cohort of PD patients. One-hundred-fifty-four PD patients were included in the study. Female PD patients (n = 62) exhibited a higher prevalence of sleep problems than males (n = 92), with nocturnal motor-related sleep issues being the most frequent. Sleep disturbances differently correlated with a range of NMS between the two sexes. In females, sleep problems mostly correlated with pain; on the other hand, sleep disturbances were linked to a frailer phenotype characterized by global dysautonomia, perception disturbances, and impaired cognitive function in males. Whether female PD patients experienced a lower HR-QoL than males, sleep disturbances were associated with a worse HR-QoL in both sexes. In conclusion, sleep problems in PD differently burden the two sexes, suggesting possible different etiopathogenesis, diagnostic investigations, and possibly tailored approaches.

Unraveling the interplay between environmental microplastics and salinity stress on Mytilus galloprovincialis larval development: A holistic exploration - Khouloud Boukadida; Rania Mlouka; Mohamed Rida Abelouah; Souha Chelly; Ilef Romdhani; Gea Oliveri Conti; Margherita Ferrante; Matteo Cammarata; Maria Giovanna Parisi; Aicha AitAlla; Mohamed Banni (Science of The Total Environment, 2024)

Prioritizing conservation of terrestrial orchids: A gap analysis for Italy - Michele Lussu; Leonardo Ancillotto; Rocco Labadessa; Michele Di Musciano; Piero Zannini; Riccardo Testolin; Francesco Santi; David Dolci; Matteo Conti; Michela Marignani; Stefano Martellos; Lorenzo Peruzzi; et al. (Biological Conservation, 2024)

Bioplastics on marine sandy shores: Effects on the key species Talitrus saltator (Montagu, 1808) - Tania Martellini; Alessandro Russo; Alessandra Cincinelli; Saul Santini; Cristiana Lofrumento; Matteo Baini; Samuele Ciattini; Luca Conti; Francesca Mostardini; Luca Mercatelli; Alberto Ugolini (Science of The Total Environment, 2023)

Juvenile polyposis diagnosed with an integrated histological, immunohistochemical and molecular approach identifying new SMAD4 pathogenic variants - Andrea Mafficini; Lodewijk A. A. Brosens; Maria L. Piredda; Cristian Conti; Paola Mattiolo; Giulia Turri; Maria G. Mastrosimini; Sara Cingarlini; Stefano F. Crinò; Matteo Fassan; Paola Piccoli; Michele Simbolo; et al. (Familial Cancer, 2022)
Juvenile polyposis (JP) is a rare familial syndrome characterized by the development of numerous hamartomatous polyps of the gastrointestinal tract and by an increased risk of developing gastrointestinal cancers. It follows a pattern of autosomal dominant inheritance and is associated with germline variants of SMAD4 or BMPR1A genes. Differential diagnosis may be difficult based on histology alone, due to morphological similarities to other familial syndromes. Here we report a case of familial JP diagnosed in a 50-years woman with a familial history positive for gastrointestinal cancers and other tumor types. The patient presented with severe iron deficiency anemia and showed numerous polyps in the stomach and jejunum according to endoscopy and imaging. She underwent an intra-gastric laparoscopic removal of the major gastric polyp, followed by jejunal exploration and resection of a segment with multiple neoformations. Histological examination revealed the presence of hamartomatous polyposis. Gastric and intestinal samples were analyzed with next-generation sequencing. Molecular analysis showed that the patient harbored a germline splicing site variant of SMAD4 , c.1139 + 3A > G, which was complemented by different somatic variants of the same gene in the different polyps. Immunohistochemistry for SMAD4 confirmed loss of protein expression in the polyps, with regular expression in normal cells. cDNA sequencing further confirmed the findings. We thus definitively diagnosed the woman as having JP thanks to an integrated approach based on histology, immunohistochemistry and molecular analysis. The identified variants, all previously reported as variants of unknown significance, were classified as pathogenic as they complemented each other leading to SMAD4 loss.

Clinical efficacy of different monoclonal antibody regimens among non-hospitalised patients with mild to moderate COVID-19 at high risk for disease progression: a prospective cohort study - Alessia Savoldi; Matteo Morra; Pasquale De Nardo; Anna Maria Cattelan; Massimo Mirandola; Vinicio Manfrin; Piergiorgio Scotton; Maria Teresa Giordani; Lucio Brollo; Sandro Panese; Massimiliano Lanzafame; Giovanna Scroccaro; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
This study aimed to compare the clinical progression of COVID-19 in high-risk outpatients treated with the monoclonal antibodies (mAb) bamlanivimab, bamlanivimab-etesevimab and casirivimab-imdevimab. This is an observational, multi-centre, prospective study conducted from 18 March to 15 July 2021 in eight Italian tertiary-care hospitals including mild-to-moderate COVID-19 outpatients receiving bamlanivimab (700 mg), bamlanivimab-etesevimab (700–1400 mg) or casirivimab-imdevimab (1200–1200 mg). All patients were at high risk of COVID-19 progression according to Italian Medicines Agency definitions. In a patient subgroup, SARS-CoV-2 variant and anti-SARS-CoV-2 serology were analysed at baseline. Factors associated with 28-day all-cause hospitalisation were identified using multivariable multilevel logistic regression (MMLR) and summarised with adjusted odds ratio (aOR) and 95% confidence interval (CI). A total of 635 outpatients received mAb: 161 (25.4%) bamlanivimab, 396 (62.4%) bamlanivimab-etesevimab and 78 (12.2%) casirivimab-imdevimab. Ninety-five (15%) patients received full or partial SARS-CoV-2 vaccination. The B.1.1.7 (Alpha) variant was detected in 99% of patients. Baseline serology showed no significant differences among the three mAb regimen groups. Twenty-eight-day all-cause hospitalisation was 11.3%, with a significantly higher proportion ( p 0.001) in the bamlanivimab group (18.6%), compared to the bamlanivimab-etesevimab (10.1%) and casirivimab-imdevimab (2.6%) groups. On MMLR, aORs for 28-day all-cause hospitalisation were significantly lower in patients receiving bamlanivimab-etesevimab (aOR 0.51, 95% CI 0.30–0.88 p 0.015) and casirivimab-imdevimab (aOR 0.14, 95% CI 0.03–0.61, p 0.009) compared to those receiving bamlanivimab. No patients with a history of vaccination were hospitalised. The study suggests differences in clinical outcomes among the first available mAb regimens for treating high-risk COVID-19 outpatients. Randomised trials are needed to compare efficacy of mAb combination regimens in high-risk populations and according to circulating variants.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Comparative serum bactericidal activity of meropenem-based combination regimens against extended-spectrum beta-lactamase and KPC-producing Klebsiella pneumoniae - Paolo Gaibani; Donatella Lombardo; Michele Bartoletti; Simone Ambretti; Caterina Campoli; Maddalena Giannella; Sara Tedeschi; Matteo Conti; Rita Mancini; Maria Paola Landini; Maria Carla Re; Pierluigi Viale; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Plasma concentrations of efavirenz, darunavir/ritonavir and raltegravir in HIV-HCV-coinfected patients without liver cirrhosis in comparison with HIV-monoinfected patients - Leonardo Calza; Ilaria Danese; Vincenzo Colangeli; Roberto Manfredi; Eleonora Magistrelli; Gabriella Verucchi; Matteo Conti; Roberto Motta; Pierluigi Viale (Infectious Diseases, 2015)

Is musculoskeletal pain a consequence or a cause of occupational stress? A longitudinal study - Matteo Bonzini; Lorenza Bertu’; Giovanni Veronesi; Marco Conti; David Coggon; Marco M. Ferrario (International Archives of Occupational and Environmental Health, 2015)

Heterogeneous drug target expression as possible basis for different clinical and radiological response to the treatment of primary and metastatic renal cell carcinoma: suggestions from bench to bedside - Matteo Santoni; Daniele Santini; Francesco Massari; Alessandro Conti; Roberto Iacovelli; Luciano Burattini; Giampaolo Tortora; Massimo Falconi; Rodolfo Montironi; Stefano Cascinu (Cancer and Metastasis Reviews, 2014)

Cancer determining information transmission and circulation - Matteo Conti (Cancer and Metastasis Reviews, 2007)